A new species of Pristiphora (Lygaeonematus) KONOW, 1890 on spruce from East Siberia (Hymenoptera, Tenthredinidae). - Beneš, Karel (Contributions to Entomology = Beiträge zur Entomologie, 2014)
Pristiphora (Lygaeonematus) jacutica sp. n. (female, male, larva) of the abietina–group feeding on spruce is described from Central Yakutia, East Siberia, and compared with closely related species, Pristiphora (Lygaeonematus) gerula (Konow 1904) and Pristiphora (Lygaeonematus) saxesenii (Hartig 1837). In coloration it resembles dark specimens of P. (L.) gerula but shape of the penis valve is different and females are unique in having very narrow but distinct scopa as in P. (L.) saxesenii and also larvae are more similar to those of P. (L.) saxesenii. Related species are discussed and lectotypes of P. gerula and P. saxesenii are designated.KeywordsPristiphora (Lygaeonematus) jacutica sp. n., taxonomy, larva, related species, lectotypes.Nomenclatural Actsgerula (Konow, 1904) (Pristiphora (Lygaeonematus)), LT described as Lygaeonematus gerulajacutica Beneš, 2014 (Pristiphora (Lygaeonematus)), spec. n.